Determinants of Modern Contraceptive Methods Use in Piple, Chitwan of Nepal - Shah, Rajani; Malla, Dinesh Kumar (Journal of Chitwan Medical College, 2019)
Background: Family planning contributes in preventing maternal and child mortality and empowers women. For the past ten years contraceptive prevalence rate has remained stagnant in Nepal. This study aimed at identifying the use and factors associated with modern contraceptive methods in Piple, Chitwan, Nepal. Methods: It was a cross-sectional study. Piple village development committee was selected purposively, in which two wards were randomly selected. Married women of reproductive age (n=332) of each household were interviewed. Descriptive, bivariate and multivariate analysis were performed. Results: About half (49%) of the respondents had used a modern contraceptive method. Women in the age groups 25-39 years [aOR: 2.39; 95% CI: 1.16 - 4.92] and 40-49 years [aOR: 4.67; 95% CI: 1.71 - 12.70] were more likely to use modern contraceptives compared to the women in the age group 15-24 years. Similarly, women having 3 or more living children [aOR: 2.98; 95% CI: 1.19 - 7.50] were more likely to use the modern contraceptives than women with upto two children. Women whose husbands would approve of using the contraceptives [aOR: 11.33; 95% CI: 3.93-32.62] were more likely to use the methods than those who got or perceived no approval from husband. Conclusions: Information and service on modern contraceptive methods should be focused to younger women. Involvement of husbands in family planning program would contribute to use of modern contraceptives by women.